Kajian In Silico Senyawa Turunan Pirazolina terhadap Bakteri Eschericia coli: In Silico Study of Pyrazoline Derivative Compounds against Eschericia coli Bacteria - Tri Wulan Novi; Wisnu Cahyo Prabowo; Fajar Prasetya (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2021)
The development of antibiotics is needed to overcome drug resistance. Penicillin binding protein 5 (PBP5) Eschericia coli bacteria is one of the targets because it plays a role in maintaining cell shape. Pyrazolina is a compound that contains two nitrogen atoms where the two nitrogen atoms are close together and are responsible as an antibacterial agent that can disrupt the cell wall. The target molecule was downloaded from the Protein Data Bank (www.rcsb.org) (PDB ID: 6NTZ). The grid used is 20 ? x 26? x 32? with a center of 29,731?, -9,112 ? and 35,821 ?. Based on the results of the docking that has been carried out from 10 pyrazoline derivative test compounds, the resulting binding energy varies. There are 5 pyrazoline derivative compounds having binding energy lower than the natural ligands -6.27 kcal / mol. Compound P8 has the lowest value compared to other test compounds with a binding energy value of -7.69 kcal / mol. Based on the interaction, P2 and P3 compounds have interactions that are similar to the original ligands due to the presence of Pi-Donor hydrogen bonds with the amino acids SER 73 and SER 139. The results of molecular docking studies show that pyrazoline derivatives play a role in Eschericia coli bacteria.